Tokopedia Kalbe Animal Health Digital Marketing Strategy to Increase Product Sales - Simanjuntak, Sandra Gordiola; Prida Ariani Ambar Astuti (Universitas Pelita Harapan, 2024)
The global Covid-19 pandemic has significantly impacted various sectors of life. In the economic sector, many companies have faced declines in sales, losses, and even bankruptcy. For instance, PT Agroveta Husada Dharma, a company focused on animal health, has experienced a decrease in sales for livestock due to selling prices for live chickens and cows being consistently below the cost of production. The restrictions on community activities during the pandemic have compelled companies to leverage digital technology for marketing efforts, enabling them to continue operations. This research is a qualitative descriptive study utilizing a case study method with the aim of determining the digital marketing strategies employed by Tokopedia Kalbe Animal Health to boost sales during the Covid-19 pandemic. Data collection involved in-depth interviews, participant observation, and documentation. The study's findings revealed that PT Agroveta Husada Dharma's sales increased as a result of implementing an adaptive digital marketing strategy on Tokopedia, specifically using the SOSTAC framework.